PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP SISWA - Hanifah Rahmadani; Arrofa Acesta (Jurnal Sekolah Dasar, 2017)
Abstract: This study aims to determine the effect of application of the model Problem Based Learning on the understanding of the concept of V grade students of SD Negeri Unggulan Kuningan on the subjects of Social Studies IPS concept of Nature and Artificial in Indonesia. This research is a type of Quasi Experimental Design, while the research design using Nonequivalent Control Group Design. The subjects of this study are all students of VA class which amounted to 25 students and VB which amounted to 27 students in Kuningan Elementary State Elementary School. The results showed that the model of Problem Based Learning influenced the students' concept of understanding. This can be seen from the significant differences between the two sample groups, the difference is the average value of pretest = 53.11 to 79.85 in the posttest of the experimental students' learning result. While the students' learning outcomes control group pretest average value = 49.6 to 59.4 on posttest. And based on t test results, showed that the value of t-count = 6.50 with 95% significance obtained t-tabel = 2.96. Then thitung (6.50) > t-table (2.96), meaning that the model of Problem Based Learning has a significant effect on understanding the concept of students Keywords: Problem Based Learning Model, Understanding Student Concept Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model Problem Based Learning terhadap pemahaman konsep siswa kelas V SD Negeri Unggulan Kuningan pada mata pelajaran IPS konsep Kenampakan Alam dan Buatan di Indonesia. Penelitian ini merupakan jenis Quasi Experimental Design, sedangkan desain penelitiannya menggunakan Nonequivalent Control Group Design. Subjek penelitian ini adalah seluruh siswa kelas VA yang berjumlah 25 siswa dan VB yang berjumlah 27 siswa di SD Negeri Unggulan Kuningan. Hasil penelitian menunjukkan bahwa model Problem Based Learning berpengaruh terhadap pemahaman konsep siswa. Hal tersebut dapat dilihat dari adanya perbedaan yang signifikan antara kedua kelompok sampel, perbedaannya yaitu nilai rata-rata pretest = 53,11 menjadi 79,85 pada posttest hasil belajar siswa kelas eksperimen. Sedangkan hasil belajar siswa kelompok kontrol nilai rata-rata pretest = 49,6 menjadi 59,4 pada posttest. Dan berdasarkan hasil uji t, menunjukan bahwa nilai t-hitung = 6,50 dengan signifikansi 95% diperoleh t-tabel = 2,96. Maka t-hitung (6,50) > t-tabel (2,96), artinya bahwa model Problem Based Learning berpengaruh signifikan terhadap pemahaman konsep siswa. Kata kunci: Model Problem Based Learning, Pemahaman Konsep Siswa